Proceeding of the international conference on psychology : people's search for meaning through ethnicity, culture, and religion : psychology's role in handling conflicts and sustaining harmony in multicultural society July 29-30, 2016 in Yogyakarta / editor, YB. Cahya Widiyanto, A. Harimurti - THE INTERNATIONAL conference on psychology 2016 Yogyakarta; Cahya Widiyanto, YB.; Harimurti, A. (Sanata Dharma University Press, 2017)
viii, 177 hlm. : ilus. ; 23 cm.